PENINGKATAN HASIL BELAJAR PADA MATERI SIFAT WUJUD BENDA MELALUI METODE EKSPERIMEN PADA SISWA KELAS III B MIN 2 BANTUL TAHUN PELAJARAN 2019/2020 - Sarjiati Sarjiati (Pedir Research Institut, 2022)
This research was conducted with the aim of knowing how to apply the experimental method and student learning outcomes in Class III B MIN 2 Bantul in Indonesian lessons on material properties of objects after the experimental method was applied. The research was conducted for approximately 3 months, with the research subjects being 36 students of class III B MIN 2 Bantul in the 2019/2020 school year, consisting of 16 female students and 20 male students. This research was carried out in 2 cycles, in which each cycle was carried out starting from the planning, action, and reflection stages. The results showed that the application of the experimental method could improve student learning outcomes on material properties of objects, as evidenced by the results of the actions in cycle II which showed a percentage that there was a significant increase in the value of learning outcomes even at meeting 3 in cycle 2, where 100% of students got scores. above the KKM.